Investigating the Performance Effects of UK Mergers and Acquisitions: An Accounting Data Study - Seddon, Jessica (2012)
This paper employs an accounting-data based study in order to empirically investigate the relationship between mergers and acquisitions and the resulting performance effects on firms in the UK. Particular attention is given to the impact of the relatedness, or unrelatedness of the combining firms’ business activities and industries. The main findings of this empirical investigation were that on average both the target and acquiring firms experience gains after merging, and that these gains were of comparable amounts for both firms. The gains were observed to increase over time, at least up until a three-year period after the merger was undertaken. It was found that whilst the acquiring firm initially reaped the lion’s share of these gains, after two years the target was the predominant beneficiary. The investigation illustrated that the relatedness of the two firms’ business activities, as determined by their four-digit SIC codes, had a more significant and greater positive impact on the resulting performance effects experienced by the target firm, than those experienced by the acquiring firm.